Peptidase in the plasma of mice infected with Trypanosoma brucei brucei - Knowles, G.; Black, Samuel J.; Whitelaw, D.D. (Cambridge University Press, 1987)
The plasma of mice infected with pleomorphicTrypanosoma brucei bruceicontains a peptidase which has the same electrophoretic mobility on starch gels as a parasite peptidase. An enzyme with this electrophoretic mobility was not detected in the plasma of uninfected mice. The molecular weight of this enzyme in either parasite lysate or plasma from infected mice was approximately 40000 Da when assayed on a size exclusion column using high-performance liquid chromatography. The enzyme can cleave the dipeptides leu-ala, val-leu and pro-leu, but not the dipeptide phe-ala. The enzyme also cleaved the tripeptides tyr-tyr-tyr and leu-gly-gly. Another parasite peptidase which migrates on starch gels to a different position than the above-mentioned peptidase cleaved the dipeptides leu-ala, val-leu and pro-leu but could not cleave the tripeptides tyr-tyr-tyr or leu-gly-gly. Furthermore, incubation of this parasite peptidase with normal mouse plasma at 37 °C resulted in an apparent loss of detectable activity. It is postulated that the plasma of mice modifies either the charge or enzymic activity of this peptidase. We speculate that the parasite peptidase present in the plasma of mice infected withT. bruceicould contribute to pathogenesis.